A case of multiple sclerosis diagnosed with tuberculosis during teriflunomide therapy - Gözübatık Çelik, Rabia Gökçen; Öztürk, Musa (Journal of Surgery and Medicine, 2022)
A case of pulmonary tuberculosis (TB) in a patient with multiple sclerosis (MS) receiving teriflunomide is described. A 56-year-old woman with MS started interferon beta-1a treatment in 2009. Due to side effects, her physician switched her to glatiramer acetate. Over the last three years, she opted not to continue the glatiramer acetate. At the end of 2017, her symptoms reappeared, and her radiological and clinical examination showed disease progression. Teriflunomide (14 mg/day) treatment was started, and in the 15th month of teriflunomide use, a rash on the skin, coughing, night sweating fits, weakness and back pain developed. She was diagnosed with pulmonary TB based on pulmonary examination. Her purified protein derivative (PPD) score was 22. Anti-TB therapy was initiated immediately. At last visit in January 2020, TB was discovered. Her blood tests were within normal limits. Her expanded disability status score (EDSS) score was 2.5. Subcutaneous glatiramer acetate was re-initiated. A rare case of pulmonary TB under teriflunomide use is described in this case. Teriflunomide therapy should be considered in cases in which latent TB may be re-activated.